OPTIMALISASI STRATEGI PROMOSI PROGRAM STUDI MELALUI DASHBOARD BERBASIS DATA PEMINATAN DAN ANALITIK INSTAGRAM DENGAN ICFS: OPTIMIZING STUDY PROGRAM PROMOTION STRATEGIES THROUGH INTEREST DATA-BASED DASHBOARDS AND INSTAGRAM ANALYTICS WITH ICFS - Sri Mulyani; Yunus Anis; Sunardi; Vici Tiara Anjarsari; Hersatoto Listiyono (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
This research was motivated by the need for new Study Programs (Prodi) to make fast, measurable, and data-driven promotional decisions on the main channel for prospective students, namely Instagram, while content evaluation has been sporadic and metrics are scattered. The goal is to design a framework and prototype of an Excel dashboard that integrates Instagram analytics with a focus on Reels and Carousel formats and student interest data through the ICFS (Interest Content Fit Score) metric to support editorial and promotional decisions. The method used is R&D and prototyping with a mixed methods design: a dataset of 192 TRMG IG content published between November 16, 2022, and November 4, 2025, as well as student interest survey data involving 14 active TRMG Study Program students. Instagram content data is processed into Engagement indicators (likes, comments, saves, shares), ERR (Engagement/Reach), ERI (Engagement/Impressions), ERV (Engagement/Views), paired with interest/preference surveys, the results are realized in an Excel dashboard containing KPI cards, a content leaderboard, a time/content type slicer, and an automatic ICFS calculation. The main results show an operational and low-cost prototype, empirically Reels consistently drives reach and engagement, while Carousel strengthens referral behavior (save/share). The dashboard facilitates weekly content meetings and guides a targeted composition (60% Reels, 25% Carousel, 15% Image). The implication is that this solution shortens the data-to-decision distance, standardizes the evaluation of Study Program promotional content, and provides a conceptual contribution through the formulation of ICFS and a format-based engagement measurement framework. At the same time, its practical contribution is an Excel asset that is ready to be replicated in similar vocational study programs and becomes the basis for migration to an automated web dashboard.